Analisis Pengaruh Memutuskan Menabung dengan Brand Image sebagai Variabel Mediasi - Nur Huri Mustofa; Winna Widyo Wati (el-Jizya: Jurnal Ekonomi Islam, 2021)
This research aims to find out how strong "The Influence of CSR, Shariah Governance, and Service Quality on the Decision to Save with Brand Image as an Intervening Variable" at Bank Rakyat Indonesia (BRI) Syariah KCP Ungaran. In this study using quantitative methods. This data collection method is carried out by distributing questionnaires to customers of Bank BRI Syariah KCP Ungaran. Samples were taken as many as 100 respondents, with random sampling technique. The results of the Ttest test show that in this study the variables of CSR, Shariah Governance, and Service Quality have a positive and significant effect on Saving Decisions and also the variables of CSR, Shariah Governance, and Service Quality have a positive and significant effect on Brand Image. And also from the Ftest test, the variables of CSR, Shariah Governance, and Service Quality have a positive and significant effect on Saving Decisions and on Brand Image. From the Path Test using the Sobel Test that the brand image variable is also able to mediate the CSR, Shariah Governance, and Service Quality variables on saving decisions.